KONSTRUKSI MEDIA ONLINE TENTANG REALITAS PENYEDOTAN PULSA Analisis Framming Terhadap Berita Dalam Tribunnews.com - Nugroho, Ari Cahyo (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2012)
Prepaid pulse case received attention from various media, both print, electronic or online. In media judge, this case was a part of a crime by selling consumer data. One media that give more attention to the case is Tribunnews.com, which is have a lot of online media network; compared with the other online media. In connection with this research, through Robert M Etman Framing methods, the research will see the image of the selection process by this case, and highlighting certain aspects of reality. The research results show that this case constructed a consumer fraud issues. This means, that Tribune saw this problem as categorized in the realm of law. There is a deceptive element of the operator, and in this case the defrauded party (consumer). From the overall results, Tribunnews.com news framing at the legal issues of fraud.